A cross‐continental comparison of plant and beetle responses to retention of forest patches during timber harvest. Issue 8 (27th October 2016) - Baker, Susan C.; Halpern, Charles B.; Wardlaw, Timothy J.; Kern, Christel; Edgar, Graham J.; Thomson, Russell J.; Bigley, Richard E.; Franklin, Jerry F.; Gandhi, Kamal J. K.; Gustafsson, Lena; Johnson, Samuel; Palik, Brian J.; et al.
Abstract: Timber harvest can adversely affect forest biota. Recent research and application suggest that retention of mature forest elements (retention forestry), including unharvested patches (or aggregates) within larger harvested units, can benefit biodiversity compared to clearcutting. However, it is unclear whether these benefits can be generalized among the diverse taxa and biomes in which retention forestry is practiced. Lack of comparability in methods for sampling and analyzing responses to timber harvest and edge creation presents a challenge to synthesis. We used a consistent methodology (similarly spaced plots or traps along transects) to investigate responses of vascular plants and ground‐active beetles to aggregated retention at replicate sites in each of four temperate and boreal forest types on three continents: Douglas‐fir forests in Washington, USA; aspen forests in Minnesota, USA; spruce forests in Sweden; and wet eucalypt forests in Tasmania, Australia. We assessed (1) differences in local (plot‐scale) species richness and composition between mature (intact) and regenerating (previously harvested) forest; (2) the lifeboating function of aggregates (capacity to retain species of unharvested forest); and whether intact forests and aggregates (3) are susceptible to edge effects and (4) influence the adjacent regenerating forest. Intact and harvested forests differed in composition but not richness of plants and beetles. The magnitude of this difference was generally similar among regions, but there was considerable heterogeneity of composition within and among replicate sites. Aggregates within harvest units were effective at lifeboating for both plant and beetle communities. Edge effects were uncommon even within the aggregates. In contrast, effects of forest influence on adjacent harvested areas were common and as strong for aggregates as for larger blocks of intact forest. Our results provide strong support for the widespread application of aggregated retention in boreal and temperate forests. The consistency of pattern in four very different regions of the world suggests that, for forest plants and beetles, responses to aggregated retention are likely to apply more widely. Our results suggest that through strategic placement of aggregates, it is possible to maintain the natural heterogeneity and biodiversity of mature forests managed for multiple objectives.